Art and Crime : Exploring the Dark side of the Art World - Charney, Noah; Stubbs, John (Santa Barbara, CA ; Denver, CO [etc.] : ABC-Clio, 2009)
The fundamental importance of archaeological context / Derek Fincham -- Homecomings: learning from the return of antiquities to Italy / David W. J. Gill -- Lack of due diligence and unregulated markets: trade in illicit antiquities and fakes in Hong Kong / Toby Bull -- Who is stealing all those paintings? / A. J. G. Tijhuis -- The affair of the statuettes reexamined: Picasso and Apollinaire's role in the famed Louvre theft / Silvia Loreti -- Art, terrorism, and organized crime / Bojan Dobovšek -- Fakes and deception: examining fraud in the art market / Kenneth Polk and Duncan Chappell -- Implication of art theft in the fine art insurance industry / Dorit Straus -- Four art crimes and their effect on the art trade / Noah Charney -- Trepidations of a private art collector / Judah Best -- Defending art / Colonel Giovanni Pastore -- Q & A with two innovative security directors / Dennis Ahern and Anthony Amore -- Exercises in futility: the pursuit of protecting art / Stevan P. Layne -- Security for temporary exhibitions: regular, customized, or bespoke / Dick Drent -- The quiet crime: an introduction to the world of rare book, map, and document theft / Travis McDade -- Unexpected and accessible: threats to university collections / John Kleberg -- Bringing it all back home: recovery of stolen special collections materials / Richard W. Oram and Ann Hartley -- Art theft: heralds of change in the international legal landscape / Judge Arthur Tompkins -- Economic woes, art theft, and money laundering: a perfect recipe / Dafydd Nelson -- The artifacts of wartime art crime: evidence for a model of the evolving clout of cultural property in foreign affairs / Erik Nemeth -- Why masterpieces matter: some dogmatic reflections / John Stubbs
boek